Innovative exploration and post-drilling insights from H3X well in Haizhong Sag of Beibuwan Basin - Donghui JIANG; Pengcheng YANG; Xuetong CHENG; Qian CAO; Yongqi YU; Huawei NIU (Shiyou shiyan dizhi)
The Haizhong Sag of the Beibuwan Basin has undergone decades of oil and gas exploration, but no commercial achievements have been made. Previous analysis suggested that this is primarily constrained by three key issues: indefiniteness of high-quality source rocks, unclear large-scale reservoir developing zone, and unknown profitable hydrocarbon accumulation. To achieve exploration breakthroughs in the region, key factors controlling reservoir formation were reexamined and confirmed based on basin analysis methodologies. By reconstructing the prototype basin and analyzing the characteristics of paleobathymetric, paleogeomorphology, and paleo-provenance, the study identified that the Haizhong Sag developed high-quality source rocks of the Eocene Liushagang Formation. The source-to-sink system was redefined, revealing the presence of a favorable delta-beach bar sedimentary system in the relatively flat areas of the steep slope zone of the Haizhong Sag at the distal end of the Weixinan low uplift. Guided by the exploration strategy of exploring reservoirs near major fault zones of hydrocarbon transport and reservoir development areas, the steep slope zone in the Haizhong Sag was selected as the most favorable area for future exploration. The H3X well, deployed based on this strategy, achieved production breakthrough, confirming the Haizhong Sag as a hydrocarbon-rich sag with favorable conditions for dual-source hydrocarbon supply. The oil and gas mainly originated from the deeply buried Liushagang Formation of the Haizhong Sag. Oil formed in early stage and gas formed in late stage, with two periods of accumulation. The study also confirmed that the Haizhong steep zone developed a delta-beach bar sand sedimentary system. The single layer of beach-bar sand is thin, but the accumulated thickness is large. The deep reservoirs have been significantly improved by the crack modification with better physical property. Furthermore, it clarified that the steep slope zone in the Haizhong Sag is a critical target for large-scale reserve increase in Weixi area. Two hydrocarbon accumulation systems were identified, including the upper normal-pressure structural traps as well as the lower overpressure structural and lithologic traps. The connections between sand body and fault and the development of effective reservoirs are key elements for accumulation. The high position of the Hai-3 structure is the key target for reserve expansion, while the Hai-4 structure is the priority for new breakthroughs.